양안 시신경염 형태로 발병된 비전형적 다발경화증 - 이순영; 박미라 (검안 및 콘택트렌즈 학회지, 20(4), 2021)
목적: 비전형적인 증세를 보이는 양안 시신경염 환자에서 다발경화증을 진단하고 치료한 증례를 보고하고자 한다. 증례요약: 34세 여자 환자가 3주 전 급성 척수염 증세와 2주 전 양안 시력저하 소견으로 신경과에서 다발경화증 의증하 고용량 스테로이드 정맥 요법을 받았으나 시력호전이 없어 안과에 의뢰되었다. 초진 시 최대교정시력 양안 모두 0.04, 좌안의 대구심동공운동장애와 Ishihara 색각검사에서 양안 1/17, 안저검사상 시신경유두부종은 관찰되지 않았다. 뇌 및 척수 자기공명영상의 T2 강조영상에서전두엽 피질하 백질, 양안 시신경 교차 부위 및 좌측 구후 시신경 분절, 연수와 C2에서 C5 분절에 길게 걸친 고강도 신호가 관찰되었다. 혈청검사에서 항아쿠아포린-4 항체(aquaproin-4 immunogloblin G antibody [AQP4-IgG Ab])는 음성이었다. 경구 스테로이드복용 후 1달째 양안 시력 1.0/0.8로 향상되었고, 이후 4년 동안 인터페론 베타를 유지하며 재발 없이 지내던 중 추적 소실되었다. 결론: 심한 시력저하가 동반된 양안 시신경염은 다발경화증에서 드문 형태로, 철저한 진단 과정을 통해 유사질환을 배제하여 올바른 치료를 해야 할 것이다. Purpose: We report a case of multiple sclerosis with bilateral optic neuritis that was atypical in terms of both the clinical signs and symptoms. Case summary: A 34-year-old female visited the department of neurology with a complaint of sudden-onset, left lower extremity weakness and numbness that had developed 3 weeks prior, and bilateral blurred vision that had commenced 2 weeks prior. The patient was diagnosed with multiple sclerosis and prescribed high-dose intravenous methylprednisolone for 3 days, but the blurred vision did not improve. The patient was referred to the ophthalmology department. The initial best-corrected visual acuity was 0.04 in both eyes, and the relative afferent pupillary defect test was positive for the left eye. The Ishihara color test scores were 1/17 for both eyes. No optic disc swelling was evident on fundus examination. Brain and spine magnetic resonance imaging (T2-weighted) performed during the initial visit revealed lesions of high signal intensity in the frontal, subcortical white matter; the optic chiasm; the left retrobulbar optic segment; the medulla; and the spinal C2-5 processes. Aquaproin-4 immunogloblin G antibody (AQP4-IgG Ab) was not detected in serum. One month after prescription of the oral steroid, the vision improved to 1.0 in the right and 0.8 in the left eye. The patient was lost to follow-up after prescription of interferon-beta for 4 years, without recurrence. Conclusions: Binocular optic neuritis accompanied by severe visual loss is a rare form of multiple sclerosis. A thorough diagnosis (with a focus on exclusion) is required, as is appropriate treatment. KCI Citation Count: 0